(untitled) (Journal of Dhaka National Medical College & Hospital, 2019)
Background: Fixed-combination topical products are available for the treatment of facial acne vulgaris. The benefits of combined regimens include reduced risk of antibiotic resistance and improved treatment outcomes. Fixed-combination products are reported to be effective, well tolerated and more convenient for patients than multiple individual agents. Clindamycin- BPO combinations and adapalene-BPO combinations are recommended as standard treatment strategies in treating of mild to moderate facial acne vulgaris. Various clinical studies have assessed the efficacy of those topical combination therapy for facial acne vulgaris & demonstrated significantly greater and faster results. Objective: The aim of this study was to compare the efficacy of clindamycin (1%) - benzoyl peroxide (5%) combination gel with adapalene (0.1%) - benzoyl peroxide (2.5%) combination gel in treatment of mild to moderate facial acne vulgaris. Methods: A prospective, randomized and comparative study was conducted on diagnosed cases of facial acne vulgaris aged 12 to 35 years, attending at outpatient department of Dermatology & Venereology, Dhaka National Medical College & Hospital, Dhaka from July 2017 to December 2017. A total of 60 patients of acne were selected as per inclusion & exclusion criteria and randomly divided into two groups, 30 patients in group A and 30 patients in group B. Clindamycin (1%) - benzoyl peroxide (5%) combination gel was given for 12 weeks in the group A, while adapalene (0.1%) -benzoyl peroxide (2.5%) combination gel was given to the group B patients for same duration. All the drugs were provided in the gel form. The efficacy of the drugs were evaluated at week 2, 4, 8 and 12 weeks follow up by spot counting of acne lesions on the face. The number of inflammatory lesions (pustules, papules) and non inflammatory lesions (open and closed comedones) were noted during each visit in a separate chart for each patient. All parameters were compared between two groups. Quantitative data was expressed as mean±SD. Values of the different parameters were compared to see the difference between two groups by using unparied t-test. p<0.05 was considered as significant and p>0.05 was taken as non significant. 95% confidence limit was taken as the level of significance. Results: A/BPO combination gel were more effective in reducing total acne lesions including comedones, papules & pastules than C/BPO combination gel. Conclusion: Adapalene (0.1%) - benzoyl peroxide (2.5%) combination gel is more effective than clindamycin (1%) - benzoyl peroxide (5%) combination gel in the treatment of mild to moderate facial acne vulgaris. J. Dhaka National Med. Coll. Hos. 2019; 25 (02): 30-35